The influence of frequency, intensity, volume and mode of strength training on whole muscle cross-sectional area in humans - Wernbom, M.; Augustsson, J.; Thomee, R. (Sports Medicine, 2007)
Strength training is an important component in sports training and rehabilitation. Quantification of the dose-response relationships between training variables and the outcome is fundamental for the proper prescription of resistance training. The purpose of this comprehensive review was to identify dose-response relationships for the development of muscle hypertrophy by calculating the magnitudes and rates of increases in muscle cross-sectional area induced by varying levels of frequency, intensity and volume, as well as by different modes of strength training.